(untitled) (Bangladesh Journal of Otorhinolaryngology, 2012)
Objective:To compare the outcomes of various medical treatment modalities for laryngopharyngeal reflux. Study design: Prospective study design. Methods: 150 patients were divided into three groups (A, B, C) based on the mode of intervention used for the control of LPR. Each study group enrolled 50 patients using random tables. Group A: These patients were put on a twice daily dosage of esomeprazole(20 mg b.d.) and domeperidone(10 mg b.d. ) for four months Group B: These patients were put on b.d. dosage of esomeprazole(20 mg) and domeperidone(10 mg): and also received counseling for dietary and lifestyle changes. The duration of treatment was for four months. Group C: These patients received, in addition to above, 10 mg of amitriptyline (tricyclic antidepressant) b.i.d , again for four months. Results: The success achieved in controlling LPR was defined as greater than 50 % improvement in baseline symptoms. The success achieved in Group A was 46 %, in Group B was 54 % and in Group C was 40 %. The relative change in RSI over any given period of time was significantly higher than the relative change in RFS. The relative change in RSI over first month was 30.99%, which is significantly higher than the relative change of RFS (6.39%) over the same period. The mean RSI scores during four months of treatment fell from 20.67 to 8.9 (p < 0.01) in Group A, from 23.3 to 8.6 (p < 0.01) and from 21.3 to 10.8 (p < 0.05) in Group C. The mean RFS during four months fell from 15 to 6.5 (p < 0.05) in Group A, from 16 to 6.4 (p < 0.05) and from 15 to 6.4 (p < 0.05) in Group C. Conclusions: All the three interventions had a statistically significant impact on the signs and symptoms of LPR. However, higher success rates were achieved in Group B where patients were put on a b.i.d dosage esomeprazole and domeperidone nad counseled for lifestyle and dietary changes. Paradoxically, success rates achieved in Group C was lower than other groups, possibly because of the anticholinergic effects of amitriptyline causing dry mouth and dry throat. The symptomatic improvement was seen much earlier than the improvement in laryngoscopic findings. This was evidenced by the fact that relative change in RSI was much higher than the relative change of RFS over a given period of time. If diagnosed with enough surety and certainty, patients of LPR do not need any antidepressant medications as these medications may not have any role in the treatment of same and may, however, worsen the condition owing to their anticholinergic side effects. DOI: http://dx.doi.org/10.3329/bjo.v18i1.10413 Bangladesh J Otorhinolaryngol 2012; 18(1): 42-47